SOCIAL PERCEPTION OF THE TEACHINGS OF THE QURAN IN THE CONTEXT OF EDUCATION AND SOCIETY DEVELOPMENT - Najwah Khoiro; Miftahul Husna (STAI Sebelas April Sumedang, 2022)
Abstract This study explores social perceptions of Qur'anic teachings in the context of education and social development, with a focus on how these values influence societal attitudes. A mixed-methods approach was employed, combining quantitative surveys with qualitative interviews and focus group discussions to capture both measurable trends and deeper insights. The findings indicate significant variations in perception based on demographic factors such as education level, socio-economic status, and geographic location. Urban and highly educated respondents tend to interpret Qur'anic teachings more progressively, particularly in relation to inclusive education and social justice, while rural and less educated groups emphasize traditional communal values. Statistical analysis reveals a positive correlation between perceptions of Qur'anic values and support for educational and social policies that promote equity and development. These results suggest that integrating Islamic principles into policy frameworks could foster more inclusive and sustainable social development. This study contributes to the understanding of how religious values can shape public attitudes and offers practical recommendations for the integration of Qur'anic teachings into education and social policy.